Inter- and intra-annual dynamics of photosynthesis differ between forest floor vegetation and tree canopy in a subarctic Scots pine stand - Kulmala, Liisa; Pumpanen, Jukka; Kolari, Pasi; Dengel, Sigrid; Berninger, Frank; Köster, Kajar; Matkala, Laura; Vanhatalo, Anni; Vesala, Timo; Bäck, Jaana (Agricultural and Forest Meteorology, 2019)
We studied the inter- and intra-annual dynamics of the photosynthesis of forest floor vegetation and tree canopy in a subarctic Scots pine stand at the northern timberline in Finland. We tackled the issue using three different approaches: 1) measuring carbon dioxide exchange above and below canopy with the eddy covariance technique, 2) modelling the photosynthesis of the tree canopy based on shoot chamber measurements, and 3) upscaling the forest floor photosynthesis using biomass estimates and available information on the annual cycle of photosynthetic capacity of those species. The studied ecosystem was generally a weak sink of carbon but the sink strength showed notable year-to-year variation. Total ecosystem respiration and photosynthesis indicated a clear temperature limitation for the carbon exchange. However, the increase in photosynthetic production was steeper than the increase in respiration with temperature, indicating that warm temperatures increase the sink strength and do not stimulate the total ecosystem respiration as much in the 4-year window studied. The interannual variation in the photosynthetic production of the forest stand mainly resulted from the forest floor vegetation, whereas the photosynthesis of the tree canopy seemed to be more stable from year to year. Tree canopy photosynthesis increased earlier in the spring, whereas that of the forest floor increased after snowmelt, highlighting that models for photosynthesis in the northern area should also include snow cover in order to accurately estimate the seasonal dynamics of photosynthesis in these forests. Peer reviewed